Bio-Chemical Composition, Nutrient Uptake and Dry Matter Yield of Gram as Affected by Oxalic Acid Industry Waste and Fertilizer Levels in Vertisol - Khatik, S.K.; Bhadgria, A.K.S.; Dikshit, P.R. (Asian Journal of Chemistry, 2010)
Pot culture experiments were conducted with three levels of oxalic acid industry waste i.e., 0 g, 6.6 g, and 13.2 g per pot corresponding to three levels of sulphur i.e. 0 (S0), 20 (S20) and 40 (S40) ppm of S, three levels of phosphorus 0 (P0), 40 (P40) and 80 (P80), ppm of P, two levels of starter dose of nitrogen i.e. 0 (N0) and 20 (N20) ppm of N and seed treatment with (C1) and without (C0) rhizobium culture. Results reveal that increasing levels of application of variables significantly increased the dry matter yield of gram (40 DAS) as compared to control. Similar positive increasing trend was also observed in nitrogen, phosphorus, potassium, calcium, magnesium and sulphur uptake at 40 DAS over control.